2016
DOI: 10.1080/02640414.2016.1143109
|View full text |Cite
|
Sign up to set email alerts
|

Muscle coordination during breaststroke swimming: Comparison between elite swimmers and beginners

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Vaz, J. R., Olstad, B. H., Cabri, J. M. H., Kjendlie, P.-L., Pezarat Correia, P., Hug, F. (2016). Muscle coordination during breaststroke swimming:Comparison between elite swimmers and beginners. Journal of Sports Sciences, 34, 1941Sciences, 34, -1948 AbstractThe present study aimed to compare muscle coordination strategies of the upper and lower limb muscles between beginners and elite breaststroke swimmers. Surface ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 27 publications
3
47
0
3
Order By: Relevance
“…In this section, we reported the paper of Vaz et al [ 82 ], since it provides useful guidelines for the training of beginner swimmers. Authors compared beginners and elite swimmers in terms of muscle coordination during breaststroke.…”
Section: Resultsmentioning
confidence: 99%
“…In this section, we reported the paper of Vaz et al [ 82 ], since it provides useful guidelines for the training of beginner swimmers. Authors compared beginners and elite swimmers in terms of muscle coordination during breaststroke.…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate the comparison of the set of synergies between subjects, four muscle synergies were extracted for all subjects22 ) . Table 1 shows the VAF of the number of muscle synergies and the VAF of the four muscle synergies was for the pre (VAF=91.3 ± 1.2%) and post sessions (VAF=94.6 ± 0.9%).…”
Section: Resultsmentioning
confidence: 99%
“…We selected the four modules based on Vaz et al22 ) to facilitate the comparing the modules between pre and post sessions although previous studies reported that there are five identified modules during running. On the other hand, it is suggested the possibility that long-term training changes modules23,24,25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the time lag between groups, Mann-Whitney's U-test was performed in SPSS 24.0 (IBM, Armonk, NY, USA) according to the methods used by Vaz et al (2016). The signiˆcance level was set at less than 0.05.…”
Section: Discussionmentioning
confidence: 99%